2020
DOI: 10.1007/s12649-019-00928-y
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Plasma Supported by TiO2 Catalyst for Decolourisation of Reactive Orange 16 Dye in Water

Abstract: Purpose Every advanced oxidation process (AOP) has its limitations in water purification. Novel designs with simultaneous application of different AOPs can offer better solutions for cleaner water. Methods We have comparatively studied two advanced oxidation processes (AOPs) on decolourisation of Reactive Orange 16 (RO 16) azo dye pollutant from water: gas plasma treatment by low power atmospheric pressure plasma using novel plasma needle configuration, and semiconductor heterogeneous photocatalysis using tita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Several other authors evaluated different plasma configurations for dyes removal and up to this date, most of them concluded that the best efficiency is usually achieved when oxygen is used as a working gas. The details can be found in the reports (Iervolino et al, 2019;Jiang et al, 2012;Mitrović et al, 2020;Pankaj et al, 2017;Reddy & Subrahmanyam, 2012;Ruma et al, 2013;Sarangapani et al, 2017). (Jiang et al, 2012) time, it was founded that higher concentration of H2O2 was generated in water.…”
Section: Dyesmentioning
confidence: 97%
See 2 more Smart Citations
“…Several other authors evaluated different plasma configurations for dyes removal and up to this date, most of them concluded that the best efficiency is usually achieved when oxygen is used as a working gas. The details can be found in the reports (Iervolino et al, 2019;Jiang et al, 2012;Mitrović et al, 2020;Pankaj et al, 2017;Reddy & Subrahmanyam, 2012;Ruma et al, 2013;Sarangapani et al, 2017). (Jiang et al, 2012) time, it was founded that higher concentration of H2O2 was generated in water.…”
Section: Dyesmentioning
confidence: 97%
“…Therefore, development of an effective wastewater treatment process for dye elimination had been in the focus of interest of many researchers. Recently, several plasma systems using different type of working gas (argon, air, oxygen) have been evaluated: DBD discharge with cylindrical configuration (He et al, 2018;Iervolino et al, 2019), pin to surface configuration (Kasih et al, 2019;Mitrović et al, 2020), flow reactor system (Yamada et al, 2020), corona discharge (Ruma et al, 2013), parallel plane type DBD reactor (Reddy & Subrahmanyam, 2012).…”
Section: Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…A heterogeneous photo-oxidation process effectively using TiO 2 for removal of organic water pollutants 3 , 4 , 6 , 7 and disinfection 5 , 7 was reported. Mainly, TiO 2 is inexpensive and has been combined with plasma because it has a strong oxidation power, a reasonable bandgap, nontoxicity, and stability against photo- and chemical-corrosions 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, an interesting strategy, consisting of the combination of NTP and heterogeneous catalysis, has been proposed to enhance pollutant degradation efficiency and, simultaneously, reduce the formation of reaction by-products [19][20][21]. The effect of NTP combined with catalysts enhances the generation of different types of active species (such as hydroxyls) and the activity and stability of photocatalytic materials [22][23][24][25][26]. For example, when a photocatalyst is introduced into an NTP reactor, the generation of the active species through the plasma, including ultraviolet light, can induce photocatalytic reactions, for example through the following path [27]:…”
Section: Introductionmentioning
confidence: 99%